2017
DOI: 10.3389/fpls.2017.01373
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Alleviates Damage from Heat Stress in the Photosystem II of Tall Fescue in Both the Photochemical and Thermal Phases

Abstract: L-Ascorbate (Asc) plays important roles in plant development, hormone signaling, the cell cycle and cellular redox system, etc. The higher content of Asc in plant chloroplasts indicates its important role in the photosystem. The objective of this study was to study the roles of Asc in tall fescue leaves against heat stress. After a heat stress treatment, we observed a lower value of the maximum quantum yield for primary photochemistry (φPo), which reflects the inhibited activity of the photochemical phase of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…Analysis of fluorescence parameters suggested exogenous ALA had protective effects on thylakoid membranes and PSII. Similar protective effects on PSII by exogenous application of other low‐molecular‐weight compounds, such as ascorbic acids and spermidine, were previously reported on tall fescue exposed to heat stress (Chen et al., 2017; Zhang et al., 2017).…”
Section: Discussionsupporting
confidence: 79%
“…Analysis of fluorescence parameters suggested exogenous ALA had protective effects on thylakoid membranes and PSII. Similar protective effects on PSII by exogenous application of other low‐molecular‐weight compounds, such as ascorbic acids and spermidine, were previously reported on tall fescue exposed to heat stress (Chen et al., 2017; Zhang et al., 2017).…”
Section: Discussionsupporting
confidence: 79%
“…Cd toxicity negatively affects photosynthesis by reducing chlorophyll content, which adversely influences general plant growth and development by disrupting vital metabolic processes (Kim et al, 2008;Hong et al, 2013;Jan et al, 2015;Khan et al, 2015;Jung et al, 2016Jung et al, , 2017Jung et al, , 2018bFarooq et al, 2018). Recently, some studies have demonstrated that the exogenous application of sulfur (Khan et al, 2015;Jung et al, 2017;Tian et al, 2017), glutathione (Chen et al, 2010;Mostofa et al, 2014;Kim et al, 2017;Jung et al, 2019) or ascorbate (Chen et al, 2017;Jung et al, 2018a;Semida et al, 2018;Zhang et al, 2019) may alleviate different heavy metal stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Akram et al (2017) comprehensively and systematically demonstrated that AsA plays a very important role in reducing oxidative stress by reviewing the previous reported studies that examined the effect of AsA application on numerous plants subjected to various environmental abiotic stressors including high and low temperature, drought, and salinity. Despite the fact that AsA is used in many different fields to mitigate oxidative stress induced by various environmental stressors (Akram et al, 2017;Chen et al, 2017), there are only a few studies reported on the interaction between Cd toxicity and AsA (Chao et al, 2010;Semida et al, 2018). Chao et al (2010) reported that hydroponic treatment with AsA reduces malondialdehyde (MDA) production and increases chlorophyll content, thereby contributing to reversing the effects of Cd toxicity in rice.…”
Section: Introductionmentioning
confidence: 99%
“…Arabidopsis studies revealed that an increased Asc content can limit the deleterious effects of high lightand high temperature-induced oxidative stress [137]. AsA alleviates heat stress-induced damage in tall fescue [138] and strawberry [139]. The inducible expression and activity of APX isoforms differed in sand pear cultivars exposed to heat stress, reflecting their tolerant and sensitive attributes [140].…”
Section: The Involvement Of Asc In Response To Abiotic Stressmentioning
confidence: 99%